(untitled) (Baghdad Science Journal, 2025)
During the period October 2003 till July 2004, about (253) urine samples have been collected from urinary tract infection. The study has shown that the bacterium Proteus mirabilis is the responsible for (11.85%) of the urinary tracts infections. Also, the study has declared that the ratio of separation this bacterium from women was (7.51%) and it is higher than the ratio of separation in both men and children which ranged (1. 58%) and (2.76%) respectively . About (30) samples of stool have been collected from children and the ratio of isolation this bacterium has been showen to be( 30%) from children aged bellow 3 years,as well as, we have got bacterial cultures related to P.mirabilis isolated from the infections of middle-ear and bacteremia . Morphological and biochemical studies have been applied to characterize the isolation bacterium as well as other kinds of micro-orgarisms that were isolated from infections of urinary tracts in this study. The results of the study demonstrated the bacterial isolates have shown an absolute resistance with a ratio of (100%) for both the antibiotic Ceftazidime and Cephalothin. Also, the study has shown that the antibiotic Ciprofloxacin is the most effective antibiotic against this type of bacterium . The percentage of sensitivity for the local isolates to this kind of antibiotic was (96.7%) then Gentamycin and Cephotaxim and the ratio of sensitive isolates to these antibiotics were (80%) and (76.7%) respectively. We have studied some virulence factors which the bacterium owns like the production of enzymes ?-Lactamase and Extended spectrum ?–Lactamase . The study has shown that the local isolates of this bacterium produce these enzymes with a ratio of (100 %) . The study confirmed the efficiency of fish extract agar prepared locally in growing bacterium . Also , it affirmed that the fish extract agar supplemented with (4-6 %) of sodium chloride is mimcs the appearing in C.L.E.D (cystien lactose electrolyte deficient medium